Implementation of State Defense Education in Facing the Threat of Terrorism - Mochamad Ferli Ferdiansyah; Ari Pitoyo Sumarno; Mochammmad Afifuddin (CV. AFDIFAL MAJU BERKAH, 2024)
State defense is an effort to defend the country based on love for the homeland and awareness of the Indonesian nation and state with confidence in Pancasila as the foundation of the state and based on the 1945 Constitution as the state constitution. The importance of implementing state defense education considering the threat of terrorism is still growing in Indonesia. The vulnerable group of this radical movement is the younger generation, as well as the general public in a limited manner. Of course this is a very serious threat, especially the values of state defense education and Pancasila in the younger generation are felt to have faded due to the rapidly growing globalization. In answering the above problems, this research uses a qualitative method with a descriptive analytical approach. The purpose of this paper is to find out how the implementation of state defense education in Indonesia in the face of the current threat of terrorism. Related to this, the importance of state defense education must begin early in the implementation of education, because the younger generation is the main gate for the spread of terrorism.